2002
DOI: 10.28945/360
|View full text |Cite
|
Sign up to set email alerts
|

IT Education's Failure to Deliver Successful Information Systems: Now is the Time to Address the IT-User Gap

Abstract: Executive SummaryIT curricula were created in business schools because traditional computer scientists had problems building information systems that were acceptable to the people that use them. Now, many years later, the percentage of unsuccessful information systems is still alarmingly high. Research in this area tended to be focused on the project level and seemed to ignore the growing conflict between end-users and the IT department as a whole.The IT-User gap is pervasive and takes many different forms. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…They point out that the ability to interact with all potential stakeholders in an organisation, to clearly document requirements, and to effectively express ideas has long been recognized by researchers and practitioners as critical success factors. Mann (2002) notes that there is little literature on the gap between end-users and the IT department. It has been observed that IT personnel have different personality traits than does the general population, going some way towards explaining why there is a gap.…”
Section: Historical View Of User-developer Cultural Differencesmentioning
confidence: 99%
“…They point out that the ability to interact with all potential stakeholders in an organisation, to clearly document requirements, and to effectively express ideas has long been recognized by researchers and practitioners as critical success factors. Mann (2002) notes that there is little literature on the gap between end-users and the IT department. It has been observed that IT personnel have different personality traits than does the general population, going some way towards explaining why there is a gap.…”
Section: Historical View Of User-developer Cultural Differencesmentioning
confidence: 99%